Towards a cultural history of digital autodidacticism: changing cultural narratives of education - Julian Sefton-Green (Perspectiva, 2019)
The essay argues that the various new imaginaries of the connected, creative, autonomous, coding, motivated and making digital learner have their roots in diverse and older visions of a different kind education system (especially the craft learner working in communities of practice) than that promulgated by the human-capital inspired neoliberal governmentalised States in the world today. Tracing the histories of the older imaginaries in a cultural history of autodidacticism I examine how they become incorporated by, and thus recalibrate competing visions of the “new learner of tomorrow”.